2022
DOI: 10.1002/pc.26511
|View full text |Cite
|
Sign up to set email alerts
|

Durability of basalt fibers, glass fibers, and their reinforced polymer composites in artificial seawater

Abstract: This study focused on the durability of basalt fibers, glass fibers, basalt‐fiber‐reinforced polymer (BFRP) bars, and glass‐fiber‐reinforced polymer (GFRP) bars in an artificial seawater. The specimens were immersed in the artificial seawater at 20, 40, and 60°C; the specimen immersed in distilled water at a temperature of 60°C was also used as a reference. The tensile strength of the monofilament basalt fibers and glass fibers immersed in the seawater for 90 days at a temperature of 60°C decreases by 61% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
(100 reference statements)
0
17
0
Order By: Relevance
“…Alternatively, the shear behavior of BFRP bars should show higher strength retention when using BFRP bars with smaller diameters. Thus, previous studies conducted by our group on the durability of 6‐mm‐diameter BFRP bars coated with OPC and SSC under the same immersion conditions were used for comparison here 33,47 . Additionally, an earlier investigation indicated that SSC‐coated BFRP bars exhibited more serious degradation as the coating thickness increased; thus, the TSS retention of BFRP bars with thinner coatings was expected to be greater 15 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the shear behavior of BFRP bars should show higher strength retention when using BFRP bars with smaller diameters. Thus, previous studies conducted by our group on the durability of 6‐mm‐diameter BFRP bars coated with OPC and SSC under the same immersion conditions were used for comparison here 33,47 . Additionally, an earlier investigation indicated that SSC‐coated BFRP bars exhibited more serious degradation as the coating thickness increased; thus, the TSS retention of BFRP bars with thinner coatings was expected to be greater 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, previous studies conducted by our group on the durability of 6-mm-diameter BFRP bars coated with OPC and SSC under the same immersion conditions were used for comparison here. 33,47 Additionally, an earlier investigation indicated that SSC-coated BFRP bars exhibited more serious degradation as the coating thickness increased; thus, the TSS retention of BFRP bars with thinner coatings was expected to be greater. 15 Figure 4 shows that regardless of the immersion temperature, the TSS retention of the BFRP bars coated with OPC and SSC at 180 days was already below that of the specimens coated with SSGM.…”
Section: Coating Effectsmentioning
confidence: 99%
“…This phenomenon has also been frequently reported in previous studies. For example, the shear strength of BFRP composite bars (54 MPa) is much lower than that of GFRP composite bars (62 MPa) [31]. The interface between basalt fibre and polypropylene is only 2.53 MPa, lower than the 4.07 MPa of glass fibre [32].…”
Section: Resultsmentioning
confidence: 99%
“…Jiang et al reported the same tendency regarding BFRP using epoxy matrix. [ 11 ] The research also indicated that the degradation derives from water absorption of the fiber. Consequently, water resistant matrix can utilize the potential of a basalt fiber.…”
Section: Introductionmentioning
confidence: 99%